On the margins : Roma and public services in Romania, Bulgaria, and Macedonia with a supplement on housing in the Czech Republic - Ina Zoon ; edited by Mark Norman Templeton. (Open Society Institute, 2001)
"A call to action to improve Romani access to social protection, health care, and housing."Donated by the Open Society Institute.